2015
DOI: 10.1091/mbc.e14-08-1310
|View full text |Cite
|
Sign up to set email alerts
|

The RhoGEF DOCK10 is essential for dendritic spine morphogenesis

Abstract: Rho GTPases are crucial regulators of dendritic spine morphogenesis. However, a clear picture of the RhoGEFs activating Rho GTPases during this process is lacking. Gene expression profiling of purified Purkinje cells is used to identify the RhoGEF DOCK10 as essential for spine morphogenesis, activating a Cdc42-mediated pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 49 publications
5
32
0
Order By: Relevance
“…Statins modulate the activity of Rho GTPases, which contributes to the induction of the Th2 phenotype and ameliorates disease severity in an animal model of MS [30]. Finally, DOCK10 is also involved in dendrite spine morphogenesis [31]. Taken together with the present results, these findings implicate DOCK-10 in increased MS disease activity through its effects on lymphocyte migration and their differentiation to the Th2 phenotype, and B cell activation.…”
Section: Discussionsupporting
confidence: 76%
“…Statins modulate the activity of Rho GTPases, which contributes to the induction of the Th2 phenotype and ameliorates disease severity in an animal model of MS [30]. Finally, DOCK10 is also involved in dendrite spine morphogenesis [31]. Taken together with the present results, these findings implicate DOCK-10 in increased MS disease activity through its effects on lymphocyte migration and their differentiation to the Th2 phenotype, and B cell activation.…”
Section: Discussionsupporting
confidence: 76%
“…A closely related homolog of Ephexin5, Ephexin1 displays GEF specificity that is regulated by its phosphorylation state. Similarly to Ephexin5, Ephexin1 has been shown to target RhoA, but is also capable of activating Cdc42 and Rac1 (Shamah et al, 2001; Sahin et al, 2005), both of which enhance spine density (Tashiro et al, 2000; Wiens et al, 2005; Wegner et al, 2008; Kim et al, 2013; Ueda et al, 2013; Dhar et al, 2014; Raynaud et al, 2014; Evans et al, 2015; Jaudon et al, 2015; Kim et al, 2015; Valdez et al, 2016). Phosphorylation of Ephexin1 by Src kinase, however, causes a shift in Ephexin1 affinity away from Rac1 and Cdc42 towards RhoA, a switch which mediates EphA4-dependent growth cone collapse through RhoA activation (Shamah et al, 2001; Sahin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several small GTPases have been characterized as enhancers of spine density, especially Cdc42 (Tashiro et al, 2000; Wegner et al, 2008; Kim et al, 2013; Jaudon et al, 2015) and Rac1 (Tashiro et al, 2000; Penzes et al, 2001; Penzes et al, 2003; Tolias et al, 2007; Bacon et al, 2013; Ueda et al, 2013; Dhar et al, 2014; Raynaud et al, 2014; Evans et al, 2015; Jaudon et al, 2015; Kim et al, 2015; Valdez et al, 2016); others have been shown to inhibit spine density, in particular Ras (Yang et al, 2013; Lee et al, 2016) and RhoA (Tashiro et al, 2000; Margolis et al, 2010; Alder et al, 2013; Kim et al, 2015). Furthermore, modulators of activity for Ras (Pham and Rotin, 2001), Cdc42 (Hayakawa et al, 2008; Yamaguchi et al, 2008), and RhoA (Margolis et al, 2010; Lin et al, 2011; Papadimitriou et al, 2012) have been shown to be degraded by the proteasome, as well as Rac1 (Torrino et al, 2011; Zhao et al, 2013) and RhoA themselves (Wang et al, 2003; Cheng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These are membraneassociated proteins that are thought to transform extracellular receptor-mediated signals into an intracellular response, prominently the organization of the actin cytoskeleton. Among others, the Rho/rac/CDC42 signaling machinery is thought to be involved in activity-dependent changes in postsynaptic spines (39)(40)(41). Therefore, it is plausible that RhoGAPs and RhoGEFs act as downstream effectors for cell adhesion signals.…”
Section: Synaptic Vesicle Exocytosis and Intracellular Signal Transdumentioning
confidence: 99%